PENGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN STUDI KASUS PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BEJ TAHUN 2008-2011. - Budiatmo, Agung (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Capital structure decision to influence the value of the company to date is still the actual issues in financial management. That there was no influence of the capital structure decision of enterprise value or not there is a difference of companies use debt in the capital structure of the company not using debt. The use of debt would give tax subsidies to the company's benefits to the optimal point, but when the optimal point exceeds the menurunakn value of the company. But that in the use of funding sources the company sorts the smallest risk in that is starting from the capital itself (internal capital), the issuance of debt and equity capital Structure (external) is the sum of short-term debt balance of permanent, debt, preferred stock, and common stock. Every company analyzes a number of factors, and then set the targeted funding structure. This Target is always changing in accordance with the changing conditions, but at any time the company management there is shadow dibenak of targeted funds structure.Based on the calculation that the capital structure does not affect the value of the company. This is an indication that investors in Indonesia is not paying attention to the source of funding for the company but was more worried about how the use of such debt efficiently so as to increase the kemampulabaan of the company. Based on these findings, then companies can increase the use of debt in its capital structure.As long as the debt is able to provide larger benefits compared to costs arising from the use of debt.